Metrics of clonidine utilization in maintenance hemodialysis patients - M., Sarita; K., Praveen Kumar; P., Rama Mohan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Clonidine is less frequently used by nephrologists. Data on clonidine prescribing trends in hemodialysis patients is sparse. We assessed the clonidine utilization metrics from the case records of patients undergoing maintenance hemodialysis. Methods: In this retrospective chart review, we analysed the clinical records of hemodialysis patients using clonidine. We evaluated the frequency of clonidine use, mean dose of clonidine and percentage of patients receiving a particular dose. Additionally, we also correlated dose of clonidine with anti-hypertensive pill count. Results: A total of 70 hemodialysis patients case records were screened. All 70/70 (100%) of them were hypertensive. Only 25/70 (35.74%) of patients were prescribed clonidine as an anti-hypertensive agent. The mean clonidine dose was 352±171 µg. Majority of patients 9/25 (36%) received 400 µg of clonidine. The dose of clonidine was prescribed in the order 400 µg (36%)>200 µg (32%)>600 µg (16%)>100 µg (8%)>300 µg (4%)=700 µg (4%). There was a statistically significant correlation in the strength of clonidine prescribed with increasing anti-hypertensive drugs (p<0.05). Conclusions: In our study, we observed that 80% of our hemodialysis patients were non responders to either systolic blood pressure or diastolic blood pressure or both. Oral clonidine use was observed in 35.74% of our hemodialysis patients. There was a linear trend showing an increased dose of clonidine with an increase in the anti-hypertensive pill count.